How many children live with adults with opioid use disorder?. (September 2019) - Bullinger, Lindsey Rose; Wing, Coady
Abstract: Emerging evidence indicates the opioid crisis is affecting children, but the possible scope of the indirect effects has not been estimated. In this study, we estimate the number of children living in households with adults with opioid use disorder, and compare trends in inappropriate opioid use in households with and without children. We combined adult opioid misuse and abuse information from the National Survey of Drug Use and Health (NSDUH) with household size data from the American Community Survey (ACS). From 2002 to 2017, the number of children living with adults who misuse opioids fell from 3.43 million to 3.33 million. The number of children living with an adult with opioid use disorder increased by 30%, from 423, 000 to 548, 000. The number of children living with an adult who uses heroin increased by 200%, from 59, 000 to 198, 000. Previous research suggests that parental substance abuse damages child health and development. Downstream effects of increased parental opioid use disorder may have long-lasting implications for child development and well-being. Highlights: We estimate the number of children living with adults inappropriately using opioids. In 2017, there were 548, 000 children living with an adult with opioid use disorder. Since 2002, children living with an adult with opioid use disorder increased by 30%. The number of children living with an adult who uses heroin increased by 200%. Increased parental opioid use may have long-term implications for child welfare.